Map-based cloning and characterization reveal that an R2R3 MYB gene confers red glume in wheat - Weiwei Mao; Xiaobo Wang; Yongming Chen; Yongfa Wang; Liang Ma; Xiaoming Xie; Xiaojia Wu; Jin Xu; Yuqi Zhang; Yue Zhao; Xuejun Tian; Weilong Guo; et al. (Crop Journal)
Pigment accumulation is an important trait related to wheat domestication, but there remains a limited understanding of its molecular mechanism. The genetic control of the red glume trait by a dominant allele, Rg-B1, on 1BS was reported in the last century, but the underlying gene and its molecular basis remained elusive. Here, we identified TraesTSP1B01G005700 (G57) encoding an R2R3-MYB transcription factor (TF) as the candidate Rg-B1 gene controlling red glume color by a combination of genome-wide association study (GWAS), bulked segregant RNA-sequencing (BSR-Seq), map-based cloning, and RNA-seq. The Rg-B1 locus had zero to five duplicate copies only one of which had high transcriptional activity. Genetic evidence suggested that promoter sequence variation in G57 in the glume leads to high expression of G57, resulting in the red glume phenotype. G57 could bind to the promoters of anthocyanin synthesis genes TaCHS, TaF3ʹH, and TaUFGT, activating their expression and contributing to anthocyanin accumulation in wheat glume. G57 also played a pivotal role in up-regulating expression of genes TaDREB1C and TaFLO2 associated with increased grain weight, thereby causing increased grain weight. Our research offers a better understanding of the molecular basis of red glume in bread wheat.